Inhibition of CSF1R, a receptor involved in microglia viability, alters behavioral and molecular changes induced by cocaine - Maria Carolina Machado da Silva; Giovanni Freitas Gomes; Heliana de Barros Fernandes; Aristóbolo Mendes da Silva; Antônio Lúcio Teixeira; Fabrício A. Moreira; Aline Silva de Miranda; Antônio Carlos Pinheiro de Oliveira (Scientific Reports, 2021)
Abstract Different data suggest that microglia may participate in the drug addiction process as these cells respond to neurochemical changes induced by the administration of these substances. In order to study the role of microglia in drug abuse, Swiss mice aged 8–9 weeks were treated with the CSF1R inhibitor PLX3397 (40 mg/kg, p.o.) and submitted to behavioral sensitization or conditioned place preference (CPP) induced by cocaine (15 mg/kg, i.p.). Thereafter, brains were used to evaluate the effects of CSF1R inhibition and cocaine administration on morphological, biochemical and molecular changes. CSF1R inhibition attenuated behavioral sensitization, reduced the number of Iba-1+ cells and increased ramification and lengths of the branches in the remaining microglia. Additionally, both cocaine and PLX3397 increased the cell body to total cell size ratio of Iba-1+ cells, as well as CD68+ and GFAP+ stained areas, suggesting an activated pattern of the glial cells. Besides, CSF1R inhibition increased CX3CL1 levels in the striatum, prefrontal cortex and hippocampus, as well as reduced CX3CR1 expression in the hippocampus. In this region, cocaine also reduced BDNF levels, an effect that was enhanced by CSF1R inhibition. In summary, our results suggest that microglia participate in the behavioral and molecular changes induced by cocaine. This study contributes to the understanding of the role of microglia in cocaine addiction.